High Expression of Somatostatin Receptors 2A, 3, and 5 in Corticotroph Pituitary Adenoma - Felix Behling; Jürgen Honegger; Marco Skardelly; Irina Gepfner-Tuma; Ghazaleh Tabatabai; Marcos Tatagiba; Jens Schittenhelm (International Journal of Endocrinology)
The development of somatostatin analogs for the treatment of pituitary Cushing’s disease has been based on somatostatin receptor expression analyses of small cohorts of pituitary adenomas. Additionally, the classification of pituitary adenomas has recently changed. To enable progress with this treatment option, we assessed somatostatin receptors in a large cohort of corticotroph and other pituitary adenomas according to the new WHO classification of endocrine tumors. Paraffin-embedded tumor samples of 88 corticotroph pituitary adenomas and 30 nonadenomatous pituitary biopsies were analyzed after processing into tissue microarrays and immunohistochemical staining for SSTR 1, SSTR2A, SSTR3, SSTR4, and SSTR5. For comparison, 159 other noncorticotroph pituitary adenomas were analyzed. SSTR3 expression was higher in corticotroph adenomas compared to PIT-1-positive, gonadotroph, and nonfunctioning pituitary adenomas (p<0.0001, p=0.0280, and p<0.0001, respectively). This was also the case for the expression of SSTR5 (p=0.0003, p<0.0001, and p<0.0001, respectively). SSTR2A expression was higher compared to gonadotroph and nonfunctioning pituitary adenomas (p=0.0217 and 0.0126, respectively) while PIT-1-positive adenomas showed even higher SSTR2A expression (p<0.0001). SSTR2A and SSTR5 were both expressed higher in nonadenomatous pituitary biopsies than in pituitary adenomas (p=0.0126 and p=0.0008, respectively). There are marked expression differences of SSTR1-5 as well as changes in expression in recurrent disease that need to be addressed when looking for other possible substances for the treatment of Cushing’s disease. SSTR2A, SSTR3, and SSTR5 seem to be most suitable biomarkers for a targeted therapy with somatostatin analogs.